Three-dimensional working model of M1 RNA, the catalytic RNA subunit of ribonuclease P from Escherichia coli. - Westhof, E (1994)
A three-dimensional model of M1 RNA, the catalytic RNA subunit of RNase P from Escherichia coli, was constructed with the aid of a computer. The modeling process took into account data from chemical and enzymatic protection experiments, phylogenetic analysis, studies of the activities of mutants, and the kinetics of reactions catalyzed by the binding of substrate to M1 RNA. The model provides a plausible picture of the binding to M1 RNA of the tRNA domain of a precursor tRNA substrate. The scissile bond and adjacent segments of the aminoacyl acceptor stem of a precursor tRNA substrate can fit into a cleft that leads to the phylogenetically conserved, central part of the structure.